Cultural Intelligence, Leadership Effectiveness, and Conflict Management in Energy Diplomacy: The Case of Türkiye in the Eastern Mediterranean - Ateş, Ahmet (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
This article reviews peer-reviewed scholarship published between 2010 and 2024 to evaluate how Türkiye’s cultural-intelligence-driven leadership has shaped conflict management in Eastern Mediterranean energy diplomacy. Drawing on the four dimensions of Cultural Intelligence—cognitive, behavioural, motivational, and metacognitive—the study maps these capacities onto transformational, situational, and adaptive leadership models. It codes emergent themes through qualitative content analysis. Evidence from key inflection points—such as the 2019 Türkiye-Libya maritime accord, NATO-facilitated de-escalation efforts, and post-Ukraine-war supply-chain disruptions—suggests that a high cognitive CQ equips Ankara to anticipate rivals’ legal and diplomatic moves, while behavioural CQ enables fluid shifts between naval signalling and conciliatory rhetoric. Motivational CQ appears to sustain engagement despite exclusion from structures like the East Mediterranean Gas Forum, and metacognitive CQ accelerates strategic course corrections. In combination with a transformational–adaptive leadership blend, these competencies expand Türkiye’s bargaining space and preserve its narrative of becoming a regional energy hub. However, persistent trust deficits and maritime jurisdiction disputes still impose structural constraints. The article proposes a “CQ-Based Leadership and Conflict-Management Framework” intended to inform multi-party resource-governance strategies for both states and energy firms.